ChemInform Abstract: Ba2Cd(B3O6)2: A Congruent‐Melting Compound with Isolated B3O6 Units. Issue 30 (4th July 2013) - Zhou, Zhongxiang; et al., et al.
Abstract Powders of the title compound are prepared by solid state reaction of stoichiometric mixtures of Ba(NO3)2, CdO, and H3BO3 (810 °C, 48 h).